2013
DOI: 10.1378/chest.12-1616
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Functional Lung Heterogeneity in COPD Using Reference Equations for CT Scan-Measured Lobar Volumes

Abstract: OPD is characterized by emphysematous destruction of the lung parenchyma and remodeling of the distal small airways. [1][2][3] Emphysema is associated with hyperinfl ation, and the combination of emphysema and airway disease leads to gas trapping on exhalation. The degree to which these abnormalities exist for the whole lung can be easily assessed by either plethysmographic-or helium dilution-based measures of lung volume and regression models for predicted values derived from populations of healthy nonsmokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
(22 reference statements)
4
10
0
Order By: Relevance
“…The two latter spirometric measures of lung function were expressed as percent of predicted values . Total lung capacity (TLC) was measured using CT scan …”
Section: Methodsmentioning
confidence: 99%
“…The two latter spirometric measures of lung function were expressed as percent of predicted values . Total lung capacity (TLC) was measured using CT scan …”
Section: Methodsmentioning
confidence: 99%
“…No other similarly large cohort of nonsmokers is available for validation of the full-lung equations, although the authors of a recent publication on lobar volumes visualized on CT scans of smokers found somewhat similar differences by sex, height, and African-American race/ ethnicity, but not age and body mass index (other racial and ethnic groups were not included) (37).…”
Section: Original Researchmentioning
confidence: 99%
“…Indeed, researchers in small studies have suggested that percent emphysema varies among healthy never-smokers by demographic factors (33)(34)(35)(36); however, these studies were limited by modest sample sizes, restricted racial and ethnic distributions, and lack of population-based sampling. Investigators in a larger study recently reported that lobar lung volumes on CT scans vary by sex, height, and race (37); however, that study included mostly older smokers, who are unlikely to have structurally normal lungs, and the researchers did not address percent emphysema or total lung volumes.…”
mentioning
confidence: 99%
“…However, only two studies with comparatively small sample sizes (22,436 and 8,033) included Asian participants, and neither of these studies is from People’s Republic of China. Only the normal range of LAA%(-960 HU),29 LAA%(-950 HU),2931,3439 LAA%(-912 HU),33 LAA%(-910 HU),36 Perc 15,29,35 and mean lung attenuation30,32,33,35,37 have been reported, and these indices are inadequate for differentiating ILD from poorly aerated normal lungs.…”
Section: Introductionmentioning
confidence: 99%